Variability, correlation and path co-efficient studies in interspecific crosses (Avena sativa × A. sterilis) of oat - Bichewar Nagesh1*, A. K. Mehta1, Kadthala Bhargava2 and S. Ramakrishana1 (Electronic Journal of Plant Breeding, 2022)
Genetic variability, correlation and path coefficients for fifteen agro-morphological traits were studied on 100 oat lines including two checks. Genotypic and phenotypic coefficients of variation were high for leaf number per tiller and weight of panicle. Traits such as tiller number per plant, leaf number per tiller, weight of panicle, stem width, leaf width, individual plant yield, length of internode and thousand seed weight showed high heritability accompanied by high genetic advance indicating that these characters can be enhanced by simple selection. Association studies revealed a positively significant association of individual plant yield with thousand seed weight, floret number per panicle, spikelet number per panicle, weight of panicle, height of plant, length of internode at the phenotypic level. Path analysis disclosed that weight of panicle, width of flag leaf, floret number per panicle, tiller number per plant and length of flag leaf exhibited a positive direct effect on seed yield. Among these characters, weight of panicle, thousand seed weight, height of plant and floret number per panicle possessed positive association and direct effect. So, these traits can be used for creation of plant ideotypes and selecting these traits will be worthwhile for higher yield.